Integration of Musical Arts to Build Cooperation Skills of Elementary School Students - Lina Adi Perwitasari (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2024)
This study aims to integrate karawitan art into Cultural Arts and Crafts (SBDP) subjects as a method to instill cooperation character in students. Karawitanart, as a traditional Indonesian musical art that is rich in cultural values, has great potential to shape students' positive character, especially the character of cooperation. Through learning activities that involve karawitanensemble practice, students are invited to practice understanding the role of individuals in a group, listening, and supporting each other in achieving musical harmony. This study used the classroom action research (PTK) method conducted in several learning cycles with elementary school students in Central Java. The results showed that the integration of musical arts in SBDP subjects effectively improved students' cooperation character. Students become more active in participating, able to communicate well, and help each other to achieve common goals. This integration not only enriches cultural arts learning but also provides meaningful experiences for students to understand the importance of cooperation in everyday life.